Três ensaios sobre o mercado global de transporte marítimo de carga em contêiner - Schunke, Jaqueline Castegnaro (2020)
The first essay of this paper analyzes how the change in the configuration of service offerings in the global maritime container market impacts the price of international freight on the ten main trade routes in Asia. The increase in the capacity of ships, aiming at gains in scale, generated a global idleness of services. To reduce the effects of service idleness, shipping companies have consolidated into three major alliances, leading the market to an oligopoly status. Through an econometric model of price definition, the role of supply and demand was evaluated in the short term. The results indicate that the markets behave in different ways, that the expected scale gains in the increase in the capacity of the ships may have the opposite effect and that the incidence of ex-post rates in the regions and routes with greater volume do not allow the offer and demand operates in balance, resulting in an oligopoly structure in the sector. The second essay of this work analyzes how the variation of international maritime freight in containers influences bilateral trade relations in Brazil in the period from 2011 to 2018 on a monthly basis. The article identifies the long-term and mutual causal relationship between the value of containerized sea freight and the value traded by Brazil with abroad, in total import and export and by region. Time series methods with panel data, unit root test, Granger causality and Vector Auto-regressive model (VAR) were used. The results shows that the values of international freight negatively impact the import and export of Brazil with its commercial partners, mainly in cases where the traded merchandise is of low added value (basic goods), presenting different results only in the import from Europe and on export to North America. The opening of the Brazilian market in the 1990s allowed the internationalization of the economy with the entry of new foreign companies in the country. However, the level of openness of the Brazilian economy is still lower than that of other developing countries, participating with less than 2% of international trade. The third essay of this work analyzes how an efficiency shock at Brazilian ports would impact on different economic sectors in Brazil. The precariousness of the Brazilian port sector has long been pointed out by businessmen as one of the greatest obstacles to the circulation of wealth through exports and imports. To achieve the proposed objective, the Computable General Equilibrium (EGC) model was used, based on the GTAP (Global Trade Analysis Project) model, version 9, which uses the base year of 2011. The results show that the efficiency shock at port sector mainly stimulates Brazilian imports, with a direct impact on the increase in consumption, responsible for an increase of 60% in the increase in GDP.